The Role of Social Capital of Riau Women Farmer Groups in Building Collective Action for Tropical Peatland Restoration - Jalil, Ashaluddin; Yesi, Yesi; Sugiyanto, Seger; Puspitaloka, Dyah; Purnomo, Herry (Forest and Society, 2021)
Collective action is important when the activities and costs of restoration cannot all be internalized by the government or when urgent maintenance is required beyond the scope of the restoration project. Collective action can be influenced by social capital. In this study, we examine components of social capital and the factors that affect them. Using key informant interview, household survey, and participant observation, we also identify the extent to which social capital is related to collective action. We found that women farmer groups have high social capital, which has led to strong collective action. Social capital in Dompas’ women groups is characterized by the norms of trust and reciprocity. Strong trust and reciprocity are driven by shared culture and values and supported by kinship. Social capital arises from and is reflected in the interactions between individuals in the group. It is naturally embedded within the community, supported by strong motivation and commitment, primarily to improve the family welfare. The social capital established influenced and drove collective action, which contributes to successful management of the women farmer groups’ action arena. This paper highlights the evidence of social capital and its relation to collective action in a case from restoration in the Global South. We suggest that for a restoration action to successfully mobilize voluntary, active participation from the community, the intervention should be designed with an emphasis on establishing social capital.